Frozen Storage Characteristics of Oratosquilla nepa - Rajeswari, Tanuja; M., Shahul Hameed (Fishery Technology, 2025)
The stomatopod, Oratosquilla nepa was quick frozen as whole and as meat at -40"C and stored at -l 'C. The shelf life was evaluated by following biochemical, physical and organoleptic changes that occurred during storage. Total bacterial count was found to show a progressive fall for 3 months. Trimethyl amine values were found to decrease after 6 months of storage. Highest values for total volatile nitrogen were observed after 6 months of storage. Organoleptic quality was acceptable up to 5 months. Frozen squilla stored for 5 months can be used for further processing into value added products.